In vivo antinociceptive and anti-inflammatory activities of dried- and fermented-processed virgin coconut oil. - Zakaria, Zainul Amiruddin; Somchit, Muhammad Nazrul; Mat Jais, Abdul Manan; Lay, Kek Teh; Salleh, Mohd Zaki; Long, Kamariah; Abdullah, Muhammad Nazrul Hakim (Karger: Open Access Journals, 2011)
Objective: The present study was carried out to investigate the antinociceptive and anti-inflammatory activities of virgin coconut oil (VCO) produced by theMalaysian Agriculture Research and Development Institute (MARDI) using various in vivo models. Materials and Methods: Two types of VCOs, produced via standard drying (VCOA) and fermentation (VCOB) processes were used in this study. Both VCOA and VCOB were serially diluted using 1% Tween 80 to concentrations (v/v) of 10, 50 and 100%. Antinociceptive and anti- inflammatory activities of both VCOs were examined using various in vivomodel systems. The antinociceptive activity of the VCOs were compared to those of 1% Tween 80 (used as a negative control), morphine (5 mg/kg) and/or acetylsalicylic acid (100 mg/kg). Results: Both VCOA and VCOB exhibited significant (p < 0.05) dose-dependent antinociceptive activity in the acetic acid-induced writhing test. Both VCOs also exerted significant (p < 0.05) antinociceptive activity in both phases of the formalin and hot-plate tests. Interestingly, the VCOs exhibited anti-inflammatory activity in an acute (carrageenan-induced paw edema test), but not in a chronic (cotton-pellet-induced granuloma test) model of inflammation. Conclusion: The MARDI-produced VCOs possessed antinociceptive and anti-inflammatory activities. Further studies are needed to confirm these observations.